A New Database on Trait-Based Selection of Stormwater Pond Plants - Gisele P. Nighswander; Mary E. Szoka; Kayla M. Hess; Eban Z. Bean; Gail Hansen; Basil V. Iannone (EDIS)
Stormwater ponds play critical roles for flood control and water quality treatment, and they can provide ecological services to communities. Those ecological services can be enhanced with proper pond design and maintenance. This 6-page fact sheet written by Gisele P. Nighswander, Mary E. Szoka, Kayla M. Hess, Eban Z. Bean, Gail Hansen de Chapman, and Basil V. Iannone III and published by the UF/IFAS School of Forest Resources and Conservation provides a comprehensive database of plant traits to help readers make informed stormwater pond plant selection decisions based on their own relative priorities. https://edis.ifas.ufl.edu/fr416